The rise and fall of promises: a preliminary method to trace promises in science and technology - Stefan D. M. Gaillard; Sanda Hachana (Journal of Responsible Innovation)
Nanoscience has faced several scandals since its inception, with Theranos being the most recent. This scandal resulted from continuous overpromises and deceptive promises, practices not uncommon in science. Promises foster mutual confidence and cooperation, but to remain reliable, breaking them must have consequences. One such consequence is decreased reputation, for example through scandal. Although the Theranos scandal exposed the harms of overpromising and deceptive promises, methods to identify and monitor promises remain scarce. Such methods would allow analysis of the literature to detect broken promises over time. To address this gap, we develop a method to trace promises over time using a training corpus of nanobiology documents. This corpus was queried through the CQPweb system. We combined query development with the corpus metadata to enable the analysis when promises were made. Further integration of this method with other analytical tools could help ensure that consequences follow more quickly from over-promising.